Spider diversity in a rice agroecosystem and adjacent areas in southern Brazil - RODRIGUES, EVERTON N. L.; DE S. MENDONÇA, Jr, MILTON; OTT, RICARDO (Revista Colombiana de Entomología, 2009)
Spiders are one of the most numerous groups of terrestrial predators and these are found in diverse environments such as agroecosystems and nearby areas. Research on spider diversity in agroecosystems is important for following changes in fauna brought about by management. This work evaluated spider richness, abundance, and species composition similarity between a rice agroecosystem and adjacent environments at different development stages of the crop. The study area was Estação Experimental do Arroz, in Cachoeirinha, Rio Grande do Sul state, south Brazil. A sweep net was used with 50 passes per transect as a sample; transects were set in a rice field, in a grassland (a former rice field), and in a nearby forest edge. We sampled 2,717 spiders; 78.7% were young and most adults were females (1.22:1). Representatives of 15 families were collected, the most dominant being Oxyopidae (n = 753) and Araneidae (n = 371). Representatives of 85 morphospecies (adults) were sampled, with the most abundant being Oxyopes salticus (n = 120) and Alpaida veniliae (n=62). Most species were found on the forest edge (62), followed by rice crop (38) and grassland (26). There were significant differences in spider species composition among environments and rice culture periods. Only eight morphospecies were common to all areas; forest edge had the higher number of exclusive species (42). Rice had a typical composition of species, probably due to the ecological selectivity of the spiders. Diversity was higher in the forest edge, suggesting this environment as an important refuge for the fauna living in areas with high anthropogenic disturbance as agroecosystems.